Mapping Discourse of Food and Beverage Advertisements on Television Based on Language Structure and Function - Ikhwatun Muslimah; Yuniarti; Nurlela; Roma Ayuni A. Loebis (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
This research presents the structure and function of food and beverage advertisements on television. The method used is a discourse analysis approach in qualitative research. Descriptive analysis approach is used in the research process. The data used are food and beverage advertisements on television that contain the structure and language functions of advertisements. The research data include words, phrases, clauses, and sentences in food and beverage advertisements on television. The findings of this research illustrate that (1) the structure of food and beverage advertisements on television consists of main points, explanatory points, and closing points, and (2) the language functions in food and beverage product advertisements on television include informative, persuasive, and image-building functions to create a positive image of the product to potential consumers. Keywords: discourse analysis, oral discourse, advertisements